Pengaruh Leverage, Ukuran Perusahaan, Dewan Komisaris dan Kepemilikan Manajerial Terhadap Kinerja Keuangan - Sari, Dwi Buana; Istanti, Sri Layla Wahyu (Pascasarjana STIE Amkop Makassar, 2025)
Because financial success serves as a gauge for company advancements, it is a crucial component of accomplishing the objectives of the business. studies intended to demonstrate how management ownership, board of commissioners, company size, and leverage affect food and beverage companies' financial performance from 2020 to 2022. “In this study, the dependent variable is financial success, and the independent factors are leverage, business size, board of commissioners, and management ownership. The sample population consists of all food and beverage companies that were listed on the IDX in the years 2020–2022. The data collection technique for the study used purposeful sampling to create a sample that was suitable for the investigation. As a whole, eleven businesses provided thirty-three observations for the study. Prior to evaluating regression using usual assumptions, the data analysis method utilised multiple linear regression analysis to obtain relevant data for the study.” According to the findings, the scale of the company significantly improves financial performance, whereas managerial ownership and leverage have negligible good effects and the board of commissioners has negligible negative effects. Keywords: leverage, company size, board of commissioners, managerial ownership, financial performance.